2019
DOI: 10.1002/cssc.201900010
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of a Composite Electrode to Realize a High‐Performance All‐Solid‐State Battery

Abstract: A potential solid electrolyte for realizing all‐solid‐state battery (ASB) technology has been discovered in the form of Li10GeP2S12 (LGPS), a lithium superionic conductor with a high ionic conductivity (≈12 mS cm−1). Unfortunately, the achievable Li+ conductivity of LGPS is limited in a sheet‐type composite electrode owing to the porosity of this electrode structure. For the practical implementation of LGPS, it is crucial to control the pore structures of the composite electrode, as well as the interfaces betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…[ 180 ] Recently, more studies have demonstrated that LiNbO 3 was a better choice due to the higher ion conductivity than that of Li 4 Ti 5 O 12 , [ 181 ] which can even suppress the SCL effects at high‐voltage LiNi 0.5 Mn 1.5 O 4 /LGPS interfaces. [ 182 ] In addition, some other oxides have also been employed as effective interlayers to suppress SCLs, such as the LiNb 0.5 Ta 0.5 O 3 or LiTaO 3 layer at LiCoO 2 /LGPS interface, [ 183 ] Li 3 PO 4 layer at LiCoO 2 /80Li 2 S·20P 2 S 5 interface, [ 184 ] ZrO 2 or LiAlO 2 layer at LiNi 1/3 Mn 1/3 Co 1/3 O 2 /Li 3 PS 4 interface, [ 185 ] [Py14][TFSI] ion liquid layer at LiNi 0.8 Mn 0.1 Co 0.1 O 2 /LGPS interface, [ 186 ] LGPS/LiNbO 3 double layer at LiCoO 2 /LGPS interface. [ 187 ]…”
Section: Interfaces In All‐solid‐state Lithium Batteriesmentioning
confidence: 99%
“…[ 180 ] Recently, more studies have demonstrated that LiNbO 3 was a better choice due to the higher ion conductivity than that of Li 4 Ti 5 O 12 , [ 181 ] which can even suppress the SCL effects at high‐voltage LiNi 0.5 Mn 1.5 O 4 /LGPS interfaces. [ 182 ] In addition, some other oxides have also been employed as effective interlayers to suppress SCLs, such as the LiNb 0.5 Ta 0.5 O 3 or LiTaO 3 layer at LiCoO 2 /LGPS interface, [ 183 ] Li 3 PO 4 layer at LiCoO 2 /80Li 2 S·20P 2 S 5 interface, [ 184 ] ZrO 2 or LiAlO 2 layer at LiNi 1/3 Mn 1/3 Co 1/3 O 2 /Li 3 PS 4 interface, [ 185 ] [Py14][TFSI] ion liquid layer at LiNi 0.8 Mn 0.1 Co 0.1 O 2 /LGPS interface, [ 186 ] LGPS/LiNbO 3 double layer at LiCoO 2 /LGPS interface. [ 187 ]…”
Section: Interfaces In All‐solid‐state Lithium Batteriesmentioning
confidence: 99%
“…Zhang et al [ 285 ] prepared LGPS via planetary ball milling followed by heating. In addition, Kim et al [ 286 ] conducted studies on ionic liquids and LGPS composites. Few attempts were made to improve the structural stability of the LGPS lattice via Ba, Al, or Si doping.…”
Section: Sulfide Solid Electrolytesmentioning
confidence: 99%
“…Noteworthy advances have been made with regard to improving the contact between the SE and active electrode materials, and some selected approaches are summarized in Figure 4. [146][147][148] To ensure conformal solidsolid contacts, SEs could be coated on the surface of active materials via a solution-processable technique prior to electrode fabrication (Figure 4a). A one-step process was also proposed for making sheet-type, thick electrodes, which involved the mixing of SE precursors (e. g., Li 2 S and P 2 S 5 ) with active materials using nitrile butadiene rubber and tetrahydro- 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 furan to make the SE-electrode slurry.…”
Section: Strategies To Improve Interfacial Properties Of Composite Elmentioning
confidence: 99%
“…Second, the interfacial resistance arises from the poor solid‐solid contact induced by the different mechanical properties of SEs and active materials. Noteworthy advances have been made with regard to improving the contact between the SE and active electrode materials, and some selected approaches are summarized in Figure . To ensure conformal solid‐solid contacts, SEs could be coated on the surface of active materials via a solution‐processable technique prior to electrode fabrication (Figure a).…”
Section: Key Technologies For Solid‐state Lithium Batteriesmentioning
confidence: 99%
See 1 more Smart Citation